Herbal formula Huangqi Guizhi Wuwu decoction attenuates paclitaxel-related neurotoxicity via inhibition of inflammation and oxidative stress - Zhangming Lv; Jiayun Shen; Xuejiao Gao; Yonglan Ruan; Jinying Ling; Rongwei Sun; Jingya Dai; Haizhen Fan; Xiaolan Cheng; Peng Cao (BMC, 2021)
Abstract Background Paclitaxel-induced peripheral neuropathy (PIPN) is a challenging clinical problem during chemotherapy. Our previous work found that herbal formula Huangqi Guizhi Wuwu decoction (HGWD) could reduce oxaliplatin-induced neurotoxicity. However, its effect on PIPN remains unknown. In this study, we aim to investigate the therapeutic effect and the underlying mechanisms of HGWD against PIPN with pharmacological experiment and network pharmacology. Methods Male Wistar rats were used to establish an animal model of PIPN and treated with different doses of HGWD for 3 weeks. Mechanical allodynia, thermal hyperalgesia and body weight were measured to evaluate the therapeutic effect of HGWD on PIPN rats. On the day of the sacrifice, blood, DRGs, sciatic nerve, and hind-paw intra-plantar skins were collected to assess neuroprotective effect of HGWD on PIPN. Next, network pharmacology was performed to decipher the potential active components and molecular mechanisms of HGWD, as were further verified by western blotting analyses in PIPN rats. Finally, the effect of HGWD on the chemotherapeutic activity of paclitaxel was evaluated in vitro and in vivo. Results In rats with PIPN, HGWD reversed mechanical allodynia, thermal hyperalgesia, and ameliorated neuronal damage. Moreover, HGWD significantly increased the level of nerve growth factor, dramatically reduced IL-1β, IL-6, TNF-α levels and oxidative stress. Network pharmacology analysis revealed 30 active ingredients in HGWD and 158 candidate targets. Integrated pathway analysis identified PI3K/Akt and toll-like receptor as two main pathways responsible for the neuroprotective effect of HGWD. Further experimental validation demonstrated that HGWD expectedly inhibited the protein expression of TLR4, MyD88, IKKα, and p-NF-κB, and promoted PI3K, p-Akt, Nrf2, and HO-1 level in dorsal root ganglia. Last but not least, HGWD did not interfere with the antitumor activity of paclitaxel both in in vitro and in vivo models. Conclusion These combined data showed that HGWD could inhibit paclitaxel-evoked inflammatory and oxidative responses in peripheral nervous system viaTLR4/NF-κB and PI3K/Akt-Nrf2 pathways involvement. The neuroprotective property of HGWD on PIPN provides fundamental support to the potential application of HGWD for counteracting the side effects of paclitaxel during chemotherapy.